Belanja Pemerintah dan Peningkatan Sumber Daya Manusia di Indonesia - Adhitya Wardhana; Bayu Kharisma; Dita Selyna Sulandari (LPPM Universitas BSI, 2021)
This study aims to analyze the effect of government spending on increasing the human development index (HDI) in Indonesia. The research method used in this study is the Fixed Effect Model and the Random Effect Model with 33 provinces in Indonesia. The results showed that government spending on the functions of the economy, health, education, and infrastructure had a statistical and significant effect on the human development index. In addition, the results of each component of the human development index (life expectancy, average length of schooling, and income per capita) have a significant effect. Expenditures on education, health, economy and infrastructure need to be considered by the government by increasing capital expenditures for the purposes of human resource capacity. In addition, investment in human capital in the form of research and development is devoted to the dropout community. Meanwhile, anti-corruption enforcement in the public sector must be increased so that the budget used for human resource development can run effectively and efficiently, especially human capital development. The contribution of this research is that it has never been carried out in an inter-provincial scope in Indonesia. Keywords: government expenditure, HDI, panel data